Ethical issues in the end of life care for cancer patients in iran. - Mina Mobasher; Nouzar Nakhaee; Mamak Tahmasebi; Farzaneh Zahedi; Bagher Larijani (Tehran University of Medical Sciences, 2013)
In the recent years, advances in medical technologies for end stage cancer patients' care have affected the end-of-life decision-making in clinical practice and exposed oncologists to serious ethical dilemmas. But little is known about oncologists' viewpoints in our country regarding their ethical problems in this mention. We aimed to clarify the ethical dilemmas which Iranian oncologists may face in our health care setting and to determine factors influencing decision-making process.In this qualitative study, a phenomenological approach was used. We interviewed 8 cancer specialists in teaching hospitals in Iran and used content analysis to identify codes and categorize themes in the data.DURING THE PROCESS OF ANALYSIS, THREE MAIN THEMES EMERGED ABOUT ETHICAL DILEMMAS IN END OF LIFE CARE FOR ADVANCED CANCER PATIENTS: illness factors, socio-cultural context and patient-physician relationship. Cancer specialists identified ethical problems on several main issues, the most important of which were telling the truth in Iranian cultural context, uncertainty in end stage definition, multidisciplinary team working and cost consideration in Iranian health care system.Health care and insurance system in Iran face to end of life care challenges; therefore, health care providers and policy makers need to allocate appropriate resources and programs to improve quality of care in terminal stages. Appropriate physicians' communication skills training, multidisciplinary team working and supplementary insurance services that provide essential health care can improve the quality of care of patients with end stages of cancer. The findings of this study can help us to provide ethical policies for decision-making in end-of-life care.